2019
DOI: 10.1155/2019/6464521
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus- (EBV-) Immortalized Lymphoblastoid Cell Lines (LCLs) Express High Level of CD23 but Low CD27 to Support Their Growth

Abstract: Epstein-Barr virus (EBV) is one of the common human herpesvirus types in the world. EBV is known to infect more than 95% of adults in the world. The virus mainly infects B lymphocytes and could immortalize and transform the cells into EBV-bearing lymphoblastoid cell lines (LCLs). Limited studies have been focused on characterizing the surface marker expression of the immortalized LCLs. This study demonstrates the generation of 15 LCLs from sixteen rheumatoid arthritis (RA) patients and a healthy volunteer usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…After several weeks in culture, outgrowth of a single cell phenotype was observed. The rapid expansion indicated that cells have entered the stage of exponential proliferation, and the growth pattern showing cell clumping and rosette morphology ( 42 ) was suggestive of a proliferating lymphocytic population ( Figure 1A ). Cells were continuously propagated in vitro for an average of 15 weeks, until stably maintained.…”
Section: Resultsmentioning
confidence: 99%
“…After several weeks in culture, outgrowth of a single cell phenotype was observed. The rapid expansion indicated that cells have entered the stage of exponential proliferation, and the growth pattern showing cell clumping and rosette morphology ( 42 ) was suggestive of a proliferating lymphocytic population ( Figure 1A ). Cells were continuously propagated in vitro for an average of 15 weeks, until stably maintained.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the expression of FCER2 is increased in JNK‐deficient mice, which increases the level of FCER2‐dependent NO (Zhao et al, 2017). FCER2 can promote proliferation of Epstein Barr virus‐immortalized lymphoblastoid cell lines (Yap et al, 2019). According to the human protein database, FCER2 is mainly expressed in human SSCs of the testis.…”
Section: Discussionmentioning
confidence: 99%
“…Immortalizing B cells is an effective method for inducing the long-term growth of some human B cells in laboratory conditions [ 84 ]. In fact, this virus can immortalize cells and convert them into lymphoblastoid cell lines that carry EBV [ 85 ]. These cells effectively induce specific T cell responses against EBV in laboratory conditions due to the presentation of viral antigens [ 86 ].…”
Section: Immortality and A Review Of Its Techniquesmentioning
confidence: 99%